Post and Core Treatment to Refit Telescopic Crown-Retained Dentures after Abutment Tooth Fracture: An Evaluation of Therapy by Retrospective Survival Analysis - Vogler, Jonas Adrian Helmut; Abrahamian, William; Reich, Sarah Marie; Wöstmann, Bernd; Rehmann, Peter; Justus Liebig University Giessen (My University, 2024)
Telescopic crown-retained dentures (TCDs) are one of the most common types of prosthetic restorations for partially edentulous patients; however, post and core (PC) treatment shows the worst survival probability if the tooth is used as an abutment for the TCD. Due to extra axial forces, abutment tooth fracture is a common cause of failure for TCDs; thus, PC treatment is often needed to refit the existing telescopic crown (TC). However, there are no clinical survival data on whether the PC treatment was used to refit the TC after abutment tooth fracture (PC2) or the PC was already fitted at the time of TCD treatment (PC1). A total of 246 patients with 399 PC treatments were retrospectively evaluated for follow-ups up to 17.33 years. The files were analysed for PC1 and PC2. Furthermore, the influence of the jaw, type of tooth, luting material, PC material, bone attachment, therapist and cause of failure was recorded. For statistical analysis, Kaplan–Meier and Cox regression analyses were conducted. PC2 showed highly significant lower survival probabilities than PC1 (p < 0.001). Moreover, the bone attachment and the age of the patient at the time of fitting the PC crown had an influence on the survival (p < 0.001). Therefore, PC2 should be carefully discussed with the patient and PC1 should be favoured in endodontically treated abutment teeth for TCDs.
Keywords: ddc:610